Pseudo-Phocylides’ quotations in Quevedo’s Anacreón castellano (Castilian Anacreon) (Minerva, 2020)
In 1609, Quevedo translated Pseudo-Phocylides’ Sentences, which he also quoted in Anacreón castellano (Castilian Anacreon), through two fragments with a slightly modified translation. The collation of these different translations into Spanish of the work attributed to the Greek poet reveals possible stylistic reasons and a purpose of adaptation to the context in which they are included. Likewise, this analysis confirms Quevedo’s tendency to rewrite and to freely quote classic texts in Spanish.
Keywords: Focílides, filósofo griego, traducido en verso suelto castellano; Greek philosopher Phocylides, translated into Castilian in blank verse; Francisco de Quevedo; Pseudo-Phocylides; Anacreón castellano; Castilian Anacreon; translation